PERBAIKAN PROSES SEWING JUMBO BAG PADA PT SUTAN MORA TEKNOLOGI - Sitinjak, Chanro; Elsya Paskaria Loyda Tarigan (LPPM Universitas Putera Batam, 2024)
PT Sutan Mora Teknologi is manufacturing company engaged in the industry of making jumbo bags. The problem in this study is the result of curly stitch defects, stitches too edge, stitches not according to the pattern, broken stitches, jumping stitches, so it is not strong to withstand the load on the jumbo bag. The purpose of this study is to determine the cause of the defects of curly stitches, stitches too edge, stitches not according to the pattern, broken stitches, jumping stitches, so that it cannot withstand the load on the jumbo bag and to improve the sewing process of the jumbo bag. The method used in this research is the Six Sigma method with the DMAIC approach. From the results of this study, it is found that the cause of defects in curly stitches is that the lifeboat is often damaged, with an RPN value of 336, the seam is too edge is the seam position does not fit with an RPN value of 245, the seam does not fit the pattern is the seam pattern does not fit with an RPN value of 210, the seam breaks is the operator lacks knowledge with an RPN value of 256, the seam jumps is the work method is difficult to apply with an RPN value of 336. Improvements made to reduce the causes of curly stitch defects are to perform machine maintenance and replace the lifeboat with a new one, stitches too edge is to double check the stitches after completion of production and make a standard stitch distance against the edge of the jumbo bag, stitches not according to the pattern is to double check the stitches after completion of production, broken stitches is to accept sewing operators who are experienced enough, jumping stitches is to provide education / coaching to operators to provide easier working methods.